2018
DOI: 10.1155/2018/6204684
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Excision Repair Cross-Complementing mRNA Expression in Gastric Cancer

Abstract: Except for excision repair cross-complementing 1 (ERCC1), mRNA expression of the remaining ERCC genes has not been investigated in the prognosis of gastric cancer (GC). The present study aimed to explore the mRNA expression and prognostic values of each member of the ERCC family in GC patients by using the Kaplan–Meier (KM) plotter tool. The details of each ERCC family member were entered into a database and GC patients were separated into high and low expression to draw survival plots using the KM plotter. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…ERCC family genes are known to play essential roles in the NER process and DNA damage repair 36 . Previous studies have suggested that ERCC genes may be involved in the tumorigenesis of various cancer types 22 , 23 . However, the relationship between ERCC genes and tumor prognosis has not been thoroughly investigated, and the association of ERCC mutations with ICI response remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ERCC family genes are known to play essential roles in the NER process and DNA damage repair 36 . Previous studies have suggested that ERCC genes may be involved in the tumorigenesis of various cancer types 22 , 23 . However, the relationship between ERCC genes and tumor prognosis has not been thoroughly investigated, and the association of ERCC mutations with ICI response remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the expression level of ERCC family genes has been linked to cancer prognosis. For example, Zhao et al discovered that the expression level of ERCC4 correlates with overall survival (OS) in ovarian and gastric cancers 22 , 23 . ERCC5 downregulation has been identified as a biomarker for ovarian cancer prognosis and a potential therapeutic target 24 .…”
Section: Introductionmentioning
confidence: 99%
“…RAD23B, DDB1, and ERCC family genes (ERCC1, ERCC5, and ERCC6) are key genes in the NER pathway. Many studies have reported that they are significantly correlated with prognosis in different cancer types, such as colorectal cancer, pancreatic cancer, gastric cancer, and so on ( Luo et al, 2018 ; Zhang et al, 2019 ; Li et al, 2021 ). NEIL3 , PCNA , RFC3 , and POLD2 play important roles in the BER pathway which are recruited to DNA lesions and cleave and repair the damaged bases cooperatively ( Robertson et al, 2009 ; Hurst et al, 2021 ; Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zhao et al ( 32 ) reported that high expression of ERCC6 was associated with poor OS in patients with colorectal cancer who received or did not receive treatment with 5-fluorouracil. Luo et al ( 33 ) revealed that ERCC6 may be a biomarker for the prognosis of gastric cancer. Pu et al ( 34 ) demonstrated that the expression of ERCC6L was significantly correlated with the clinical survival of patients with breast and gastric cancer.…”
Section: Discussionmentioning
confidence: 99%